2021
DOI: 10.21203/rs.3.rs-246140/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Garlic (Allium sativum Linn) Mitigates Experimentally induced Hepatotoxicity and Nephrotoxicity in Commercial Chickens

Abstract: Intoxication as well as infectious and metabolic diseases resulting in liver and kidney damage are major causes of losses in poultry species. While there are no specific drugs for reversal of pathophysiology of the liver and kidney, certain herbs such as garlic have been shown to improve livability of livestock and poultry. Its probable potential at enhancing the functionality of these organs in the face of injuries/insults by intoxication was investigated. Chicken subgroup supplemented with 0.25% garlic-meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…On the other hand, Oladele et al. (2015) reported that feeding garlic to broiler chickens increases the delayed reaction of the footpad, which is a sign of stimulated cellular immunity. Kamboh et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Oladele et al. (2015) reported that feeding garlic to broiler chickens increases the delayed reaction of the footpad, which is a sign of stimulated cellular immunity. Kamboh et al.…”
Section: Discussionmentioning
confidence: 99%